An Anti-Corruption Seminar as a Form of Democratic Education to Strengthen Civic Understanding and Enhance Youth Participation in Honest Elections - Muslim, Haifa Syaidatul; Fatah, Fauzan Nurul; Arwan, Artiarini Puspita (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service activity aims to deepen the understanding of residents and youth in Mojopuro about anti-corruption values as part of healthy democratic education. A seminar themed “The Spirit of Democracy and the Role of Youth in Building Quality Character and Participation Towards a Dignified Mojopuro” was held on September 20, 2025, at the Mojopuro Village Hall, Jatiroto District, Wonogiri Regency. The event was attended by 71 participants, consisting of village officials, youth organizations, students, and the general public. The methods used included material delivery, interactive discussions, and evaluation interviews. The results showed an increase in understanding of honesty, integrity, and the importance of youth involvement in maintaining a clean and fair democracy. Participants also demonstrated positive changes in their knowledge, attitudes, and behaviors. Some even pledged to reject money politics and initiate educational activities in their respective communities. Overall, this activity successfully built collective awareness of the vital role of youth as agents of social change in creating a transparent and integrity-based political culture.